Gene-based therapies for neuromuscular disorders - Zanoteli, Edmar; França, Marcondes Cavalcante, Jr.; Marques, Wilson, Jr. (Arquivos de Neuro-Psiquiatria, 2024)
Neuromuscular diseases (NMD) include a broad group of medical conditions with both acquired and genetic causes. In recent years, important advances have been made in the treatment of genetically caused NMD, and most of these advances are due to the implementation of therapies aimed at gene regulation. Among these therapies, gene replacement, small interfering RNA (siRNA), and antisense antinucleotides are the most promising approaches. More importantly, some of these therapies have already gained regulatory approval or are in the final stages of approval. The review focuses on motor neuron diseases, neuropathies, and Duchenne muscular dystrophy, summarizing the most recent developments in gene-based therapies for these conditions.
Keywords: Gene Therapy; Muscular Atrophy, Spinal; Amyotrophic Lateral Sclerosis; Amyloid Neuropathies; Muscular Dystrophy, Duchenne